THERMAL EFFICIENCY AND COOLING FACTOR OF THERMAL CYCLES IN THERMODYNAMICS - FILÍPEK, Josef; ČERNÝ, Michal (Trends in education, 2010)
The work contains computer animations simulating functions of heat machines and cycles (lifting platform, Carnot's cycle, and indirect cycle). Operation and activity of these units is plotted into p-v, t-v and t-s diagram. and completed by necessary mathematical apparatus. Animated models show in a clear way the relevance between supplied heat and gas pv work (work done during changes in volume) in case of isochoric, isobaric, isothermal and adiabatic changes of state. The instructional presentation has been prepared as a study aid for physics lectures.
Keywords: Carnot's cycle; heat machines; thermal efficienci; animated models.